A novel blue light pumped yellow-emitting phosphor RbZnPO4:Dy3+ with satisfactory color tuning and thermal properties for high-power warm white light emitting diodes. Issue 129 (16th December 2015) - Zhu, Ge; Xin, Shuangyu
Abstract : Novel yellow phosphor RbZnPO4 :Dy 3+ with satisfactory color tuning and thermal properties for high-power white LEDs. Abstract : In order to explore a suitable yellow emission phosphor for blue light pumped high power warm LEDs, the synthesis and photoluminescence properties of novel yellow phosphors RbZnPO4 :Dy 3+ were investigated in detail through X-ray diffraction refinement and photoluminescence spectra measurement. The analysis revealed that RbZnPO4 :Dy 3+ phosphors had strong absorption around 455 nm and could exhibit dominated yellow emission at 577 nm as well as weak red emission at 665 nm due to the 4 F9/2 → 6 H13/2 and 4 F9/2 → 6 H11/2 transitions of Dy 3+ ions, respectively, with stable CIE coordinates (0.49, 0.50). The thermal quenching behaviour showed that RbZnPO4 :Dy 3+ had excellent thermal stability. The results indicated that the novel yellow phosphor RbZnPO4 :Dy 3+ could be a good candidate for high-power warm white LEDs.